High-quality HMX-coated HTPE-WPU coated spherical medicine
By using HTPE-WPU to coat high-quality HMX, the problem of poor bonding effect between the surface of the HMX particles and the adhesive interface is solved, the mechanical sensitivity is reduced, the thermal stability is improved, and the safety of cast modified double-based propellants is improved.
Patent Information
- Application Number
- CN202411815375.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-11
AI Technical Summary
As a non-reinforced filler, HMX has poor bonding effect on the particle surface and the adhesive interface, which is prone to occur similar "dewetting", resulting in a reduction in the mechanical properties of cast modified double-based propellants.
Polyethylene glycol polytetrahydrofuran block copolyether-water-based polyurethane (HTPE-WPU) is used as the coating agent, and high-quality HMX is coated by demulsification method to form a high-quality HMX@HTPE-WPU coated spherical drug.
It reduces the mechanical sensitivity of high-quality HMX, improves its thermal stability, and improves the inherent safety of cast modified double-based propellants.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a high-quality HMX@HTPE-WPU coated spherical medicine, which is mainly used for manufacturing a casting modified double-base propellant. Background Art
[0002] HMX is a nitramine explosive with excellent comprehensive performance. It has the advantages of high energy, high density, and high detonation velocity. As a high energy density material, it is widely used in the formulation of cast modified double-base propellants. However, in order to improve the energy level of cast modified double-base propellants, increasing the HMX content and reducing the binder content in the propellant formula will inevitably lead to a decrease in the mechanical properties of the propellant. At the same time, as a non-reinforcing filler, HMX has a poor interface bonding effect between the particle surface and the binder, and is prone to similar "dehumidification" phenomena, which is a weak link in the mechanical properties of the propellant. Therefore, enhancing the interfacial bonding strength between the solid filler particles and the binder is one of the technical approaches to improve the mechanical properties of cast modified double-base propellants.
[0003] Usually, HMX is modified and coated on the surface to reduce its mechanical sensitivity. "Study on the coating modification of HMX by polyacrylate" Initiators, 2015, 167(6): 40-43. A solution-water suspension method is disclosed, using polyacrylate or fluororubber as a coating agent to achieve coating modification of HMX. The impact sensitivity of a 2% fluororubber-HMX coated ball is H 50 40.2cm, 2% polyacrylate-HMX coated ball impact sensitivity H 50 53.5cm. "TEX coating and desensitization of HMX" Journal of Explosives and Propellants, 2018, 14(4): 394-398. A solution-water suspension coating method was reported using 4,10-dinitro-2,6,8,12-tetraoxa-4,10-diazatetracyclo[5.5.0.0 5,9 .0 3,11 ](TEX) and fluororubber coated HMX to reduce the sensitivity. The impact sensitivity of 3% fluororubber coated HMX is 92% and the friction sensitivity is 100%. "Friction properties of HMX coated with different adhesives" Science, Technology and Engineering, 2018, 18(29): 206-210. It is reported that the direct method was used to reduce the sensitivity of 6 adhesives (fluororubber, 202 rubber, butadiene rubber, GAP-ETPE, EVA, 68 # However, there is no literature report on the research of coating high-quality HMX with polyethylene glycol polytetrahydrofuran block copolyether-waterborne polyurethane (HTPE-WPU) to reduce its mechanical sensitivity. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a high-quality HMX@HTPE-WPU coated spherical propellant to solve the problems that HMX is used as a non-reinforcing filler in the existing propellant formula, the bonding effect between the particle surface and the adhesive interface is poor, and the phenomenon similar to "dehumidification" is easily produced. The present invention can reduce its mechanical sensitivity and improve the intrinsic safety of the cast modified bipropellant.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:
[0006] A high-quality HMX@HTPE-WPU coated spherical medicine comprises the following raw materials: high-quality octogen, polyethylene glycol polytetramethylenefuran block copolyether-waterborne polyurethane.
[0007] The present invention also includes the following technical features:
[0008] Specifically, the raw materials include the following by mass percentage: 98.0% to 99.0% high-quality octogenin, and 1.0% to 2.0% polyethylene glycol polytetrahydrofuran block copolyether-aqueous polyurethane.
[0009] Specifically, the raw materials include the following by mass percentage: 98.5% high-quality octogen and 1.5% polyethylene glycol polytetrahydrofuran block copolyether-aqueous polyurethane.
[0010] The method for preparing the high-quality HMX@HTPE-WPU coated spherical medicine comprises the following steps:
[0011] Step 1, preparation of demulsifier: mixing polyacrylamide with deionized water and stirring until the polyacrylamide is completely dissolved to obtain a polyacrylamide aqueous solution; mixing the polyacrylamide aqueous solution with a polyethyleneimine aqueous solution and stirring to obtain a mixed demulsifier;
[0012] Step 2: Coating high-quality Octogen by demulsification method: Weigh high-quality Octogen, then weigh polyethylene glycol polytetrahydrofuran block copolyether-aqueous polyurethane emulsion and add deionized water to dilute it, stir the high-quality Octogen and the diluted polyethylene glycol polytetrahydrofuran block copolyether-aqueous polyurethane at room temperature to form a suspension A; raise the temperature of suspension A from room temperature to 45°C, slowly add the mixed demulsifier solution, and continue stirring after the addition is completed to form a suspension B; filter the suspension B and wash it with deionized water to avoid demulsifier residue; place the product obtained by filtration in a water bath oven and dry it to constant weight to obtain high-quality HMX@HTPE-WPU.
[0013] Specifically, the step 1 includes:
[0014] Step 1.1, mix polyacrylamide and deionized water, and stir at 50°C until the polyacrylamide is completely dissolved;
[0015] Step 1.2, mixing the prepared polyacrylamide aqueous solution and the polyethyleneimine aqueous solution, stirring at 50° C. at a stirring rate of 300 r / min for 20 min to obtain a mixed demulsifier.
[0016] Specifically, in step 1.1, polyacrylamide and deionized water are mixed in a mass ratio of 1:1000.
[0017] Specifically, in step 1.2, the polyacrylamide aqueous solution and the polyethyleneimine aqueous solution are mixed in a mass ratio of W(PEI):W(PAM)=5:3.
[0018] Specifically, the step 2 includes:
[0019] Step 2.1, weighing high-quality octogen according to the formula amount, then weighing polyethylene glycol polytetrahydrofuran block copolyether-aqueous polyurethane emulsion and adding deionized water to dilute, and stirring the high-quality octogen and the diluted polyethylene glycol polytetrahydrofuran block copolyether-aqueous polyurethane at room temperature for 1 hour to form a suspension A;
[0020] Step 2.2, raising the temperature of suspension A from room temperature to 45°C, slowly adding the mixed demulsifier solution, and continuing stirring at a stirring rate of 300 r / min for 1 hour to avoid incomplete demulsification, to form suspension B;
[0021] Step 2.3, the suspension B was filtered and washed with deionized water for 5 times to avoid residual demulsifier;
[0022] In step 2.4, the product obtained by filtration is placed in a 50° C. water bath oven and dried to constant weight to obtain high-quality HMX@HTPE-WPU.
[0023] Specifically, in step 2.1, 10 g of high-quality octogen is weighed, and 0.5 g of polyethylene glycol polytetrahydrofuran block copolyether-aqueous polyurethane emulsion is weighed and 100 mL of deionized water is added to dilute.
[0024] Specifically, in step 2.2, 75 g of the mixed demulsifier solution is slowly added at a rate of 1 drop / s.
[0025] Compared with the prior art, the present invention has the following technical effects:
[0026] The coating material used for surface modification of high-quality Octogen particles of the present invention is polyethylene glycol polytetrahydrofuran block copolyether-aqueous polyurethane, and the prepared coated spherical propellant is insensitive and has good thermal stability; compared with ordinary HMX and high-quality HMX, the impact sensitivity of high-quality HMX@HTPE-WPU is reduced to 56%, the thermal stability is better, and the intrinsic safety of the cast modified double-base propellant is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscope photo of high-quality HMX-1@HTPE-WPU.
[0028] Figure 2 This is a scanning electron microscope photo of high-quality HMX-2@HTPE-WPU.
[0029] Figure 3 This is the TG chart of high quality HMX-1.
[0030] Figure 4 This is the TG chart of high quality HMX-2.
[0031] Figure 5 It is high quality HMX-1@HTPE-WPU.
[0032] Figure 6 It is high quality HMX-2@HTPE-WPU. DETAILED DESCRIPTION
[0033] The present invention provides a high-quality HMX@HTPE-WPU coated spherical propellant. Based on the insensitive characteristics of HTPE-WPU, it is used as a coating layer to reduce the mechanical sensitivity of high-quality HMX. HMX, as a non-reinforcing filler, has high mechanical sensitivity and is crucial to the mechanical properties and safety performance of cast modified double-base propellants. Ordinary HMX has an irregular shape, and the edge corners are relatively weakly bonded to the propellant adhesive matrix, forming a weak point in mechanical properties. Its own small amount of impurities and defects will inevitably have an adverse effect on the mechanical properties. High-quality HMX is obtained by recrystallization and surface optimization treatment of ordinary HMX, and has the following advantages: ① regular morphology, quasi-spherical; ② controllable particle size, narrow distribution; ③ high purity, few impurities; ④ high crystal regularity, few internal defects of the crystal, high density, and high particle strength. Using HTPE-WPU to coat high-quality HMX can greatly reduce the mechanical sensitivity of high-quality HMX and improve its thermal stability while maintaining the energy level. Introducing coated high-quality HMX into cast modified double-base propellants can effectively avoid the problems of mechanical and safety characteristics brought by ordinary HMX, and is an effective way to improve the microstructural integrity and mechanical properties of propellants.
[0034] The high-quality HMX@HTPE-WPU coated spherical medicine of the present invention comprises the following raw materials: high-quality octogen (HMX) and polyethylene glycol polytetrahydrofuran block copolyether-waterborne polyurethane (HTPE-WPU).
[0035] The raw materials include the following by mass percentage: 98.0% to 99.0% high-quality octogenin, 1.0% to 2.0% polyethylene glycol polytetrahydrofuran block copolyether-waterborne polyurethane. Preferably, 98.5% high-quality octogenin, 1.5% polyethylene glycol polytetrahydrofuran block copolyether-waterborne polyurethane.
[0036] The preparation method of the high-quality HMX@HTPE-WPU coated spherical medicine of the present invention comprises:
[0037] (1) Preparation of demulsifier
[0038] ① Mix polyacrylamide (PAM) and deionized water at a mass ratio of 1:1000 and stir at 50°C until the polyacrylamide is completely dissolved;
[0039] ② The prepared polyacrylamide aqueous solution and polyethyleneimine (PEI) aqueous solution were mixed in a mass ratio of W(PEI):W(PAM)=5:3, and stirred at 50°C at a stirring rate of 300 r / min for 20 min to obtain a mixed demulsifier.
[0040] (2) Demulsification method to coat high quality Octogen
[0041] ① According to the formula, weigh high-quality octogen (HMX), then weigh polyethylene glycol polytetrahydrofuran block copolyether-waterborne polyurethane (HTPE-WPU) emulsion and add 100 mL of deionized water to dilute, and stir the high-quality octogen and the diluted polyethylene glycol polytetrahydrofuran block copolyether-waterborne polyurethane at room temperature for 1 hour to form a suspension A;
[0042] ② Raise the temperature of suspension A from room temperature to 45°C, slowly add 75g of mixed demulsifier solution at a rate of 1 drop / s, and continue stirring at a stirring rate of 300r / min for 1h after the addition is completed to avoid incomplete demulsification, forming suspension B;
[0043] ③ Filter the suspension B and wash it with deionized water 5 times to avoid residual demulsifier;
[0044] ④ Place the product obtained by filtration in a 50°C water bath oven and dry to constant weight to obtain high-quality HMX@HTPE-WPU.
[0045] The polyethylene glycol polytetrahydrofuran block copolyether-waterborne polyurethane (HTPE-WPU) emulsion (solid content of 30%) used in the present invention is synthesized by Beijing Institute of Technology; high-quality HMX is prepared by Xi'an Modern Chemistry Research Institute; polyacrylamide (PAM) (cationic) and polyethyleneimine (PEI) aqueous solutions (non-ionic, solid content of 23.34%) are all provided by Ordnance Factory 845.
[0046] Specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical solution of this application fall within the protection scope of the present invention.
[0047] Embodiment 1:
[0048] This embodiment provides a high-quality HMX@HTPE-WPU coated spherical medicine and a preparation method, including:
[0049] (1) Preparation of demulsifier
[0050] ① Mix PAM and deionized water at a mass ratio of 1:1000 and stir at 50°C until PAM is completely dissolved;
[0051] ② The prepared PAM aqueous solution and PEI aqueous solution were mixed in a mass ratio of W(PEI):W(PAM)=5:3, and stirred at 50°C at a stirring rate of 300 r / min for 20 min for use.
[0052] (2) Demulsification method to coat high quality HMX-1
[0053] ① Weigh 10g of high-quality HMX-1, then weigh 0.5g of HTPE-WPU emulsion and add 100mL of deionized water to dilute, and stir the high-quality HMX-1 and diluted HTPE-WPU at room temperature for 1h to form suspension A;
[0054] Specifically, the HMX-1 in this embodiment has a regular shape and regular crystal size, with a particle size distribution of 40 μm-45 μm and an aspect ratio of 1.16;
[0055] ② Raise the temperature of suspension A from room temperature to 45°C, slowly add 75g of mixed demulsifier solution at a rate of 1 drop / s, and continue stirring at a stirring rate of 300r / min for 1h after the addition is completed to avoid incomplete demulsification, forming suspension B;
[0056] ③ Filter the suspension B and wash it with deionized water 5 times to avoid residual demulsifier;
[0057] ④ Place the product obtained by filtration in a 50°C water bath oven and dry to constant weight to obtain high-quality HMX-1@HTPE-WPU.
[0058] HTPE-WPU actual weighing value = HTPE-WPU emulsion × solid content = 0.5g × 30% = 0.15g;
[0059] High-quality HMX mass percentage = 10 / (10+0.15)×100% = 98.5%;
[0060] HTPE-WPU mass percentage = 0.15 / (10+0.15)×100% = 1.5%.
[0061] Embodiment 2:
[0062] This embodiment provides a high-quality HMX@HTPE-WPU coated spherical medicine and a preparation method. The preparation process of this embodiment is the same as that of Example 1, and high-quality HMX-2@HTPE-WPU is prepared. The difference is that the HMX-2 in this embodiment has larger crystal particles than the HMX-1 in Example 1, regular shape, uniform particle size, particle size distribution in the range of 60μm-75μm, and aspect ratio of 1.03.
[0063] In order to prove the universality of HTPE-WPU coated high-quality HMX, the present invention selects two high-quality HMXs of Example 1 and Example 2 for verification; the scanning electron microscope photos of high-quality HMX-1@HTPE-WPU and high-quality HMX-2@HTPE-WPU are shown in the figure. Figure 1 and 2 The surface of high-quality HMX particles is rough, indicating that the coating layer is evenly distributed on the surface of high-quality HMX particles and the coating effect is good.
[0064] The mechanical sensitivity of HMX, high-quality HMX and its coated samples were tested according to GJB 772A-97 method 601.1 (experimental conditions: 10 kg drop hammer, 250 mm drop height, 50 mg drug amount). The test results are shown in Table 1.
[0065] Table 1 Impact sensitivity test results
[0066] sample Impact sensitivity / % HMX 100 High quality HMX-1 92 High quality HMX-2 96 High quality HMX-1@HTPE-WPU 56 High quality HMX-2@HTPE-WPU 60
[0067] The thermal stability TG curves of high-quality HMX and high-quality HMX@HTPE-WPU are as follows: Figures 3 to 6 Compared with the thermal decomposition temperatures of high-quality HMX-1 and high-quality HMX-2 (291.4℃ and 291.5℃), high-quality HMX-1@HTPE-WPU and high-quality HMX-2@HTPE-WPU began to lose weight at a higher temperature (291.8℃), indicating that the coating material effectively isolates the external heat source, slows down the thermal decomposition process, improves the thermal stability of high-quality HMX, and enhances safety.
Claims
1. A high-quality HMX@HTPE-WPU coated spherical medicine, characterized in that: It includes the following raw materials: high-quality Octogen, polyethylene glycol polytetramethylenefuran block copolyether-waterborne polyurethane.
2. The high-quality HMX@HTPE-WPU coated spherical medicine according to claim 1, characterized in that: Calculated by mass percentage, the raw materials include: 98.0% to 99.0% of high-quality octogenin and 1.0% to 2.0% of polyethylene glycol polytetrahydrofuran block copolyether-aqueous polyurethane.
3. The high-quality HMX@HTPE-WPU coated spherical medicine according to claim 1, characterized in that: Calculated by mass percentage, it includes the following raw materials: 98.5% high quality Octogen, 1.5% polyethylene glycol polytetramethylene furan block copolyether - waterborne polyurethane.
4. The method for preparing high-quality HMX@HTPE-WPU coated spherical medicine according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1, preparation of demulsifier: mixing polyacrylamide with deionized water and stirring until the polyacrylamide is completely dissolved to obtain a polyacrylamide aqueous solution; mixing the polyacrylamide aqueous solution with a polyethyleneimine aqueous solution and stirring to obtain a mixed demulsifier; Step 2, coating high-quality Octogen by demulsification method: weigh high-quality Octogen, then weigh polyethylene glycol polytetrahydrofuran block copolyether-aqueous polyurethane emulsion and add deionized water to dilute, stir the high-quality Octogen and the diluted polyethylene glycol polytetrahydrofuran block copolyether-aqueous polyurethane at room temperature to form a suspension A; raise the temperature of suspension A from room temperature to 45°C, slowly add the mixed demulsifier solution, continue stirring after the addition is completed, and form a suspension B; filter the suspension B and wash it with deionized water to avoid demulsifier residue; place the product obtained by filtration in a water bath oven, dry to constant weight, and obtain high-quality HMX@HTPE-WPU.
5. The method for preparing high-quality HMX@HTPE-WPU coated spherical medicine according to claim 4, characterized in that: The step one comprises: Step 1.1, mix polyacrylamide and deionized water, and stir at 50°C until the polyacrylamide is completely dissolved; Step 1.2, mixing the prepared polyacrylamide aqueous solution and the polyethyleneimine aqueous solution, stirring at 50° C. at a stirring rate of 300 r / min for 20 min to obtain a mixed demulsifier.
6. The method for preparing high-quality HMX@HTPE-WPU coated spherical medicine according to claim 5, characterized in that: In the step 1.1, polyacrylamide and deionized water are mixed at a mass ratio of 1:1000.
7. The method for preparing high-quality HMX@HTPE-WPU coated spherical medicine according to claim 5, characterized in that: In the step 1.2, the polyacrylamide aqueous solution and the polyethyleneimine aqueous solution are mixed in a mass ratio of W(PEI):W(PAM)=5:
3.
8. The method for preparing high-quality HMX@HTPE-WPU coated spherical medicine according to claim 4, characterized in that: The second step comprises: Step 2.1, weighing high-quality octogen according to the formula amount, then weighing polyethylene glycol polytetrahydrofuran block copolyether-aqueous polyurethane emulsion and adding deionized water to dilute, and stirring the high-quality octogen and the diluted polyethylene glycol polytetrahydrofuran block copolyether-aqueous polyurethane at room temperature for 1 hour to form a suspension A; Step 2.2, raising the temperature of suspension A from room temperature to 45°C, slowly adding the mixed demulsifier solution, and continuing stirring at a stirring rate of 300 r / min for 1 hour to avoid incomplete demulsification, to form suspension B; Step 2.3, the suspension B is filtered and washed with deionized water for 5 times to avoid residual demulsifier; In step 2.4, the product obtained by filtration is placed in a 50° C. water bath oven and dried to constant weight to obtain high-quality HMX@HTPE-WPU.
9. The method for preparing high-quality HMX@HTPE-WPU coated spherical medicine according to claim 7, characterized in that: In the step 2.1, 10 g of high-quality octogen was weighed, and 0.5 g of polyethylene glycol polytetrahydrofuran block copolyether-aqueous polyurethane emulsion was weighed and 100 mL of deionized water was added to dilute.
10. The method for preparing high-quality HMX@HTPE-WPU coated spherical medicine according to claim 9, characterized in that: In the step 2.2, 75 g of the mixed demulsifier solution is slowly added at a rate of 1 drop / s.
Citation Information
Patent Citations
Coating explosive microspheres prepared through emulsion solidification and preparation method thereof
CN106083495A
Low-sensitivity and high-strength octogen-based composite material and preparation method thereof
CN110204403A
Nonisocyanate-cured azide polyether binder system and propellant
CN110590484A
Gap / nitramine-based energetic propellant composition having excellent mechanical properties
KR1020100035522A
Filler reinforcement of polyurethane binder using a neutral polymeric bonding agent
WO1989003372A1